2021
DOI: 10.1007/s10803-021-05355-4
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style and Mental Health Profiles of Parents Caring for a Child with Autism: Suicidal Ideation, Depression and Anxiety

Abstract: The study investigated association between attachment style of parents with a child diagnosed with Autism and mental health. A cross-sectional web-based survey collected data from 184 parents of individuals with autism. Findings from the study indicated association between an avoidant and anxious attachment style and mental health. Mainly, a link between avoidant attachment style and parents' levels of suicidal ideation and depression, an association between anxious attachment style and the parent's level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Accordingly, it is crucial to study parenting children with autism since it differs from everyday parenting [1]. A current study shows that autistic children's parents require a healthy mental state to manage an aggressive child with autism [4].…”
Section: Current Statusmentioning
confidence: 80%
See 2 more Smart Citations
“…Accordingly, it is crucial to study parenting children with autism since it differs from everyday parenting [1]. A current study shows that autistic children's parents require a healthy mental state to manage an aggressive child with autism [4].…”
Section: Current Statusmentioning
confidence: 80%
“…The primary caregiver of a child with autism is their parent [1]. Therefore, giving the children special attention is their responsibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with studies examining the experiences of mothers of children with ASD in other regions of the world [ 5 , 17 , 24 , 52 , 53 , 54 ]. These studies found that parents’ limited awareness of ASD contributed to initial reactions of denial, sorrow, fear and shock, and that parents who have children diagnosed with ASD exhibit greater levels of mental health problems such as anxiety and depression [ 18 , 19 ], as well as suicidal ideation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, 95% of parents and 93% of adults with autism reported adverse effects on their mental health[ 64 ]. In addition, several parents of children with autism committed suicide due to the severe psychological pressure and stress during the care of their children[ 65 ].…”
Section: Impact Of Covid-19 On Autism Managementmentioning
confidence: 99%